2010
DOI: 10.1258/ebm.2010.010118
|View full text |Cite
|
Sign up to set email alerts
|

Diamide decreases deformability of rabbit erythrocytes and attenuates low oxygen tension-induced ATP release

Abstract: Exposure of erythrocytes to reduced oxygen (O2) tension activates the heterotrimeric G protein Gi, resulting in accumulation of cAMP and release of ATP. The mechanism by which exposure of erythrocytes to reduced O2 tension activates Gi is not known. Here we investigate the hypothesis that, in rabbit erythrocytes, ATP release in response to exposure to reduced O2 tension requires membrane deformation. If this hypothesis is correct, then decreasing the deformability of the erythrocyte membrane should decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 44 publications
(120 reference statements)
5
45
1
Order By: Relevance
“…However, studies of the deformability of erythrocytes from humans with type 2 diabetes have yielded conflicting results (4,8,37,49). This is important, because we and others have demonstrated that reduced erythrocyte deformability can inhibit low O 2 -induced ATP release (45). Here, we examined the deformability of erythrocytes of healthy humans and humans with type 2 diabetes in the absence and presence of insulin and C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of the deformability of erythrocytes from humans with type 2 diabetes have yielded conflicting results (4,8,37,49). This is important, because we and others have demonstrated that reduced erythrocyte deformability can inhibit low O 2 -induced ATP release (45). Here, we examined the deformability of erythrocytes of healthy humans and humans with type 2 diabetes in the absence and presence of insulin and C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…5) (13, 23, 26 -28). Under this construct, exposure of erythrocytes to reduced O 2 results in hemoglobin desaturation and an associated conformational change in the hemoglobin molecule (17,34). Although the mechanism is not fully understood, this change in hemoglobin saturation/conformation results in activation of the heterotrimeric G protein G i and increases in cAMP (34).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that simvastatin treatment inhibited low O 2 tension-induced ATP release was unexpected. Previous reports (42,46) using healthy human erythrocytes have shown that there is a link between low O 2 tensioninduced ATP release and erythrocyte deformability. Thus, while Y-27632 increased both erythrocyte deformability and low O 2 tension-induced ATP release, erythrocytes stiffened with the cytoskeletal crosslinker diamide were less deformable and had impaired low O 2 tension-induced ATP release (42,46).…”
Section: Discussionmentioning
confidence: 91%
“…Such a mechanism is consistent with studies (16,37) in which shear stress was shown to activate G i in other cell types and suggests that reduced membrane deformability would decrease low O 2 tension-induced activation of G i . Importantly, previous studies have shown that reduced membrane deformability inhibits low O 2 tension-induced ATP release from erythrocytes (42,46), whereas increased deformability of these cells augments ATP release in response to this stimulus (46).…”
mentioning
confidence: 92%